Implementasi Keterampilan Dasar Konseling Guru BK SMK Kota Semarang - Hindun Sri Rahmawati; Edy Purwanto; Mulawarman Mulawarman (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2020)
The research aims: (1) to describe the level of understanding and application of basic counseling communication by school counselors, and (2) to propose an alternative to improve basic skills counseling. This research is a descriptive quantitative research. The data collection method by providing a questionnaire consisting of 30 statements on a Likert scale. Based on the test of reliability with cronbach's alpha calculation the questionnaire that was compiled had a reliability of 0.846. Analysis of the data used is descriptive statistics with quartile measurements. The study population was Semarang City Vocational School counselors, simple random sampling involving 104 people as samples. The results is the five lowest aspects of implementation are: (1) increasing the client's self-esteem; (2) planning for the final stages of counseling; (3) share what the client / counselee feels, feels and thinks with the client; (4) creating a comfortable atmosphere in the initial stages of counseling; and (5) challenge the counselee to see inconsistencies in words and actions. Increasing the professional competence of vocational school counselors in understanding and applying basic attending counseling is important. The next researcher is recommended to develop this research with different methods and more specifically on other aspects of counseling. Keywords: School Counselor,Basic Skill Counseling, Attending